Decomposing the temporary-permanent wage gap in New Zealand - Gail Pacheco; Bill Cochrane (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2015)
Recent years have seen a push for greater labour market flexibility, and an accompanying upsurge of interest in temporary employment and the negative outcomes often associated with such employment arrangements. This study focusses on the pay outcome and investigates the presence of wage discrimination against the temporary workforce in New Zealand. This country is a useful case study here, because of the very low levels of employment protection legislation afforded temporary workers, relative to the rest of the OECD. The temporary-permanent wage gap is assessed via two alternative methodologies: Oaxaca decomposition and propensity score matching (PSM). In the former of these we find that much of the wage difference is explained by observables. In contrast to this result, when we compare observably similar permanent and temporary workers (via PSM), we find evidence of a substantial pay penalty of between 12-17 percent, which varies substantially across different types of temporary employment.
Keywords: 330; temporary work; compensating wage differential; propensity score matching